Investigation on the causes of variation orders in the construction of building project - a study in the state of Selangor, Malaysia - N. Mohammad,; A.I. Che Ani,; R.A.O.K,; Rakmat,; M.A. Yusof, (Penerbit UKM, 2010)
This paper investigates the most significant causes contribute to the variation orders in the construction of building projects in the States of Selangor Malaysia. Data was collected from questionnaires survey which is based on the literature reviews and also provisions in the ‘Persatuan Akitek Malaysia” (PAM 1998) standard form of building contract that are associated with the variation orders. The data were analyzed by using mean score method and rank to formulate the findings. The result from questionnaires survey revealed three most significant causes variation orders which are: ‘Change of plan by owner’, ‘Substitution of materials by owner ’, and ‘Changes of design by consultant’. The finding concludes that owner is the major source of the variation orders in construction of building projects and suggested that owner should have adequate planning and recourses before initiating a project in order to avoid variation order during the construction stage.